An ICT-oriented Management Solution for NGNs - Gonçalves, Pedro (2012)
NGN architecture reused several standards from the IP world, as exemplified by the Session Initiation Protocol SIP, which is ubiquitous in the majority of these network components. However, the NGN management architecture simply presented a very generic management model that follows TMN. Several management technologies are proposed, such as Web services, CORBA and SNMP, to implement management solutions. Network and systems management standardizing bodies currently promote newer technologies that aim to solve known shortcomings to these. This paper proposes a management solution for NGNs based on recent IP world technologies. The presented solution was implemented in the form of a middleware to manage NGN elements. This middleware was used in the management of an element belonging to the IP Multimedia Subsystem platform, namely the Policy and Charging Rules Function.